Notch1 signalling regulates endothelial proliferation and apoptosis in pulmonary arterial hypertension. Issue 4 (28th July 2016) - Dabral, Swati; Tian, Xia; Kojonazarov, Baktybek; Savai, Rajkumar; Ghofrani, Hossein Ardeschir; Weissmann, Norbert; Florio, Monica; Sun, Jan; Jonigk, Danny; Maegel, Lavinia; Grimminger, Friedrich; Seeger, Werner; et al.
Pulmonary arterial hypertension (PAH) is characterised by excessive pulmonary vascular remodelling involving deregulated proliferation of cells in intima, media as well as adventitia. Pulmonary arterial endothelial cell (PAEC) hyperproliferation and survival underlies the endothelial pathobiology of the disease. The indispensable involvement of Notch1 in the arterial endothelial phenotype and angiogenesis provides intriguing prospects for its involvement in the pathogenesis of PAH. We observed an increased expression of Notch1 in lungs of idiopathic PAH (IPAH) patients and hypoxia/SU5416 (SUHx) rats compared with healthy subjects. In vitro loss- and gain-of-function studies demonstrated that Notch1 increased proliferation of human PAECs (hPAECs) via downregulation of p21 and inhibited apoptosis via Bcl-2 and Survivin. Inhibition of Notch signalling using the γ-secretase inhibitor dibenzazepine dose-dependently decreased proliferation and migration of hPAECs. Notably, Notch1 expression and transcriptional activity were increased under hypoxia in hPAECs and knockdown of Notch1 inhibited hypoxia-induced proliferation of the cells. Furthermore, in vivo treatment with a γ-secretase inhibitor (AMG2008827) significantly reduced the right ventricular systolic pressure and right heart hypertrophy in SUHx rats. Here, we conclude that Notch1 plays a critical role in PAH and Notch inhibitors may be a promising therapeutic option for PAH. Increased Notch1 regulates endothelial proliferation, migration and survival in PAH, making it a novel target http://ow.ly/Z7iD3008Dxn